The impact of integrated narrative therapy and imagotherapy on attitudes to marriage in marriage volunteers - Zeinab Mohamadian; Fatemeh Bahrami khondabi; Korosh Goudarzi; Masoud Sadeghi (مجله علوم روانشناختی, 2019)
Background: research has been indicated about effectiveness of narrative therapy But does the combination of narrative therapy and imagotherapy affect attitudes to marriage? Aims: The purpose of this study was to investigate the effect of the combined approach of narrative therapy and imagotherapy on marital expectations in marriage volunteers. Method: The research method is semi-experimental with experimental and control group. The statistical population of the study consisted of 80 girls and boys of marriage age in Boroujerd. Using a convenience sampling method from 60 men and women who were willing to participate in the research, a total of 60 person were selected for the experimental and control groups. The attitude to Marriage Scale (MAS) Brateen& Rosen (1998) was used for data collection. Each of the experimental groups received 8 sessions 11-minute of combined Imagotherapy and Couples Narrative Therapy (Shaver, Niener & Albert, Aurangz, 2018). Multivariate analysis of covariance was used to analyze the data. Results: The results showed that the combined approach of imagotherapy and narrative therapy on attitude to marriage (pessimistic attitude to marriage, optimistic attitude to marriage and realistic attitude to marriage) had a positive effect on both post-test and follow-up (p<0/01). Conclusions: Therefore, it is possible to use a combination of narrative therapy and imagotherapy on a realistic view of marriage in marriage volunteers.